2003
DOI: 10.1024/0036-7281.145.12.571
|View full text |Cite
|
Sign up to set email alerts
|

Aktuelle Daten zur Antibiotikaresistenz der wichtigsten bovinen Mastitiserreger in der Schweiz

Abstract: 100 strains of Staphylococcus aureus (S. aureus), 100 strains of coagulase-negative staphylococci (CNS), 100 strains of Streptococcus spp. and 100 strains of Escherichia coli (E. coli), isolated from bovine mastitis milk samples between November 2002 and April 2003, were tested for their sensitivity to various antibiotics by means of the agar diffusion method. The antibiotics were chosen on the basis of their licenses for intramammary application in Switzerland (www.vetpharm.unizh.ch). 91% of the S. aureus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
3
4
1
Order By: Relevance
“…Nonaureus staphylococci had a higher percentage of antibiotic resistance than Staphylococcus aureus, which was in agreement with previously reported data of Corti et al (2003). The number of nonaureus staphylococci that showed resistance to at least one antibiotic was higher than that described by Rajala-Schultz et al (2004).…”
Section: Antibiotic Resistance Of Nonaureus Staphylococcisupporting
confidence: 92%
See 1 more Smart Citation
“…Nonaureus staphylococci had a higher percentage of antibiotic resistance than Staphylococcus aureus, which was in agreement with previously reported data of Corti et al (2003). The number of nonaureus staphylococci that showed resistance to at least one antibiotic was higher than that described by Rajala-Schultz et al (2004).…”
Section: Antibiotic Resistance Of Nonaureus Staphylococcisupporting
confidence: 92%
“…De Oliveira et al (2000) found only a low level of antibiotic resistance of bovine mastitis pathogens from Europe and the United States. In Switzerland, there was no increase of antibiotic resistance of mastitis pathogens during the last 20 yr (Corti et al, 2003). A recent review found no evidence that antibiotic therapy has led to a problem of resistance in mastitis-causing bacteria (NMC, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although coliform pathogens had good overall susceptibility to gentamicin, cefoperazone and amoxicillin clavulanic acid ranging from 83.3 to 90.3 %, a considerable proportion of the isolates were resistant. This signals a change from earlier studies in which all investigated coliforms were sensitive to these drugs (Corti et al, 2003) or resistances were seen in less than 3 % of isolates (Moser et al, 2013). The susceptibility prevalences calculated in this study were subject to a selection bias and are not in consistence with a recently published study (Moser et al, 2013).…”
Section: Discussioncontrasting
confidence: 65%
“…This was surprising because ten years earlier, the prevalence of penicillin-resistant Staph. aureus isolates was only 9 % in Switzerland (Corti et al, 2003), and 16.4 % (Overesch et al, 2013) and 20 % (Kretzschmar et al, 2013) in more recent studies. The prevalence of penicillin-resistant Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation